The Effect Of A Balance Of Tapioka And Wheat Flour On The Level Of Likes Of Dumbo Catfish Meatballs - Junianto, Junianto; M.A, Abshar; Ahmad Y, Fathan; Dwi C, Angga; A, Ghanialy (Barakuda 45: Jurnal Ilmu Perikanan dan Kelautan, 2024)
One fish that has various benefits and an interesting taste is the African catfish (Clarias gariepinus). African catfish meat can be processed into meatball products. The level of liking for meatballs can be influenced by the type and amount of filling ingredients used. The aim of this research is to determine the balance of tapioca flour and wheat used in making African catfish meatballs to produce the most preferred product. The research method used was experimental with a completely randomized design consisting of 4 balanced treatments of tapioca and wheat flour, namely 100%: 0%; 90% : 10%; 80% : 20%; and 7% : 30%. The four treatments were repeated 15 times according to the number of panelists used. The parameters observed were the level of preference for the appearance, taste, aroma and texture of African catfish meatballs. Testing the level of liking was carried out using a hedonic test. The panelists used were 15 semi-trained panelists. The data were analyzed using the Friedman test to determine the effect of treatment on the level of preference for the appearance, taste, aroma and texture of African catfish meatballs. If there is an effect then proceed with the Multiple comparison test to determine the differences between treatments. The Bayes method was used to determine the best treatment. Based on the research results, the best treatment was obtained from a balance of tapioca flour and wheat at 70% and 30%. The dombu catfish meatballs obtained from this treatment had an average level of preference for appearance, aroma, texture and taste of 6.06 (usual - like); 6.06 (regular - like); 6.06 (regular - like); and 5.66 (usual- like).